Answer:
2 Fe(iii)2O3 + 3 C ==> 2 Fe + 3 CO2
Step-by-step explanation:
First of all, you have to translate the words into an equation.
Fe(iii)2O3 + C ==> Fe + CO2
The easiest way to tackle this is to start with the Oxygens and balance them. They must balance by going to the greatest common factor which is 6. So you multiply the molecule by whatever it takes to get the Oxygens to 6
2 Fe(iii)2O3 + C ==> Fe + 3 CO2
Now work on the irons. There 2 on the left and just 1 on the right. So you need to multiply the iron by 2.
2 Fe(iii)2O3 + C ==> 2 Fe + 3 CO2
Finally it is the turn of the carbons. There are 3 on the right, so you must make the carbon on the left = 3
2 Fe(iii)2O3 + 3 C ==> 2 Fe + 3 CO2
And you are done.